Making Things Collectively. (17th February 2023) - Paek, Chaeyoung
In this paper, I examine two different kinds of production processes, mass production and collaborative production . While both production processes intuitively seem like collective actions, the established views about collective action fail to treat them as collective action due to the common issue: the lack of shared intention. As an alternative, I propose the artifactual view of action, according to which collective action is possible even when there is no shared intention among agents. Motivated by Evnine's (2016 ) view about action, the artifactual view of action claims that we can have other people's actions as matter out of which we create our own action. I argue that the artifactual account of action can successfully explain mass production as collective action. Furthermore, it provides a way for the intention-dependent views about artifacts to better understand how mass-produced artifacts come into existence.